Design, comparison and selection of two competition incentive mechanisms - Dahai Li; Huan Wang; Jingcheng Ye (PLoS ONE, 2026)
When facing multiple agent teams, principals often implement competitive mechanisms to mitigate moral hazard. These mechanisms can be categorized as either result-oriented or process-oriented, depending on their operational focus. This paper analyzes the optimal incentive contracts offered by principals to agents under these two competitive modes. Furthermore, to mitigate potential conflicts arising from these mechanisms, the matching of agents with varying abilities is also considered. Our analysis reveals that both competitive modes can effectively incentivize agent effort. However, excessive result-oriented competition can be detrimental to the principal’s benefits, suggesting that its intensity should be carefully calibrated. Moreover, when forming agent pairs, a “strong-weak” pairing is preferable to a “strong-strong” pairing, which, in turn, is preferable to a “weak-weak” pairing. Finally, this paper discusses the scope of application for each competition-incentive system. These findings provide a foundation for effectively utilizing competitive mechanisms to enhance the principal’s returns.